Thermal distortion analysis of head slider - Zhang, Yu Mei (2008)
Thermal influence becomes more significant in the reliability research of hard disk read write (R/W) head technology with the geometry of the R/W head becoming smaller. Thermal distribution and thermal distortion of head slider, which is induced by writing current during the writing process, is discussed in this project.